2007
DOI: 10.1093/geront/47.supplement_1.51
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and Assisted Living

Abstract: Purpose: This article presents an overview of what is known about dementia services in assisted living settings and suggests areas for future research. Design and Methods: We undertook a search of Medline, the Journals of Gerontology, and The Gerontologist. We then organized publications dealing with the target subject into 10 topic areas and reviewed them. Results: The article describes the demographic characteristics of cognitively impaired residents in assisted living and related residential settings in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 74 publications
(65 reference statements)
0
28
0
Order By: Relevance
“…Research with people with dementia in extra care housing is a relatively new field of endeavour (Hyde et al, 2007). Outcome measures in this context are in development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research with people with dementia in extra care housing is a relatively new field of endeavour (Hyde et al, 2007). Outcome measures in this context are in development.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States the term assisted living settings is used. In a review of research on assisted living (Hyde, Perez, & Forrester, 2007) highlighted that networks of researchers in this area are relatively new when compared to care home research and that there are significant methodological and practical issues to overcome. They concluded that much of what we know from research into care practices for people with dementia in community and nursing home settings needs to be replicated and new types of research undertaken in assisted living settings.…”
Section: Introductionmentioning
confidence: 99%
“…Under a predominately social model (Hyde et al 2007), residents receive meals and medication oversight as well as a private or shared room; assistance with bathing may be offered on a limited basis. Residents are able to manage self-grooming and toileting, although they often require mobility aides.…”
Section: Introductionmentioning
confidence: 99%
“…Quality of life is a primary outcome for these residents, and mealtimes including quality of food and tablemate fellowship play a significant role (Hopper et al 2007;Street et al 2007). However, more research is required to understand what influences quality of life in these care settings as they are currently understudied (Hyde et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation